The combination of Galanin (1-15) and Escitalopram decrease the alcohol selfadministration in rats through the functional network ventral tegmental area – dorsal raphe. - Flores Gómez, Marta; García-Cantero, Noelia; Flores-Burgess, Antonio; Pineda-Gómez, Juan Pedro; Serrano, Antonia; Orio, Laura; Puigcerver-Martínez, Araceli; Santín-Núñez, Luis Javier; Díaz-Cabiale, Zaida; Millón-Peñuela, Carmelo (My University, 2023)
Alcohol Use Disorder AUD is a highly prevalent, and most AUD patients suffer comorbidity with depression. To investigate the effect of GAL(1-15) on ESCmediated effect in depression-alcoholism comorbidity, we used the alcohol self-administration test. In addition, to study the circuits involved, we analyzed the immuno of C-Fos in several nuclei implicated in reward-seeking behaviour and we assessed the brain circuits using principal component analysis (PCA) to understand brain functional organization. Male Sprague-Dawley rats received three intraperitoneal injections of ESC(2.5mg/Kg) 23, 5 and 1h and icv injection of GAL(1-15)(0.3nmol) 15' before the alcohol self-administration test. The brain was removed 90' after the icv injection toanalyzed C-Fos in several nuclei involved in depression and AUD: dorsal raphe (DR), rostromedial tegmental nucleus (RMTg), lateral habenula (LHb), medial habenula (mHb), ventral tegmental area (VTA), nucleus accumbens (NAc) and prefrontal cortex (CPF). ANOVA followed by Fisher´s least significant di"erence test was used. In the alcohol self-administration test, the combination of GAL(1-15)(0,3nmol) and ESC(2,5mg/Kg) decreased the number of alcohol reinforcements and the number of active lever. GAL(1-15)+ESC coadministration significantly decreased C-Fos expression in the VTA compared with control group but no significative effects were observed in the rest of the nuclei. However, PCA analysis revealed three independent factor representing the functional brain modules. The main factor was DR, VTA and RMTg. The results indicate a functional network involved in GAL(1-15)+ESC alcohol self-administration effects. It opens up the possibility to use GAL(1-15)+ESC as a novel strategy in AUD comorbidity with depression.
Keywords: Neuropéptidos; Antidepresivos; Alcoholismo; Alcohol; Galanina (1-15); Escitalopram